FACTORS THAT INFLUENCE THE INTEREST OF ACCOUNTING STUDENTS TO BECOME EXTERNAL AUDITORS - Endang Purwaningsih; Agastasia Chrismawati (STIE St. Pignatelli Surakarta, 2020)
This research aims to analyze the influence of the intrinsic value of work, social values, work environment, personality, financial rewards, considerations job market, professional recognition, professional training on accounting student interests in choosing a career into an external audit. Samples used in 113 accounting students in the final semester or already following auditing course 1 and auditing course 2, from 7 colleges in Solo, Salatiga, Semarang, and Yogyakarta. Analysis techniques used multiple linear regression analysis. As a result of this study, the intrinsic value of the work financial rewards, and job market considerations have a significant positive effect interest in accounting students in choosing a career to be external audit. Variables of social values, work environment, personality, professional recognition, and professional training are not and insignificant to the interest of accounting students in selecting career to become an external audit.